Management goals of innovative development for institutes of Higher pedagogical education - Kharkivska, Alla (My University, 2013)
The article analyzes the existing requirements for the goals, and requirements for function purposes are formulated as well as the interrelation between management goals and goals of the educational process are defined. The author emphasizes that management goals of innovative development for higher pedagogical institutions are the result of research and prediction of changes for components in the educational system that takes into account the possibility of the system, scientific validity, innovation, consistency and feasibility of planned actions with a fixed time to achieve them, the ability to quantitatively and qualitatively assess results.
Kharkivska A. Management goals of innovative development for institutes of Higher pedagogical education / А. Kharkivska // Теорія та методика управління освітою : електрон. наук. фах. вид. / ДВНЗ "Ун-т менедж. освіти" НАПН України. – 2013. – Вип. 11. – URL : http://tme.umo.edu.ua/docs/11/4.pdf
Keywords: цілі управління, інноваційний розвиток, вища педагогічна установа; management goals, innovative development, a higher pedagogical institution; цели управления, инновационное развитие, высшее педагогическое учреждение